Active Warming during Cesarean Delivery: Should We SCIP It? - Grant, Erica N.; Craig, Margaret G.; Tao, Weike; McIntire, Donald D.; Leveno, Kenneth J. (American Journal of Perinatology, 2015)
Background The purpose of this open, cluster randomized controlled trial was to evaluate whether use of a fiber optic–regulated warming mattress would decrease the incidence of hypothermia in women undergoing cesarean delivery.Patients and Methods A total of 484 women were randomized via the cluster method on a rotating weekly basis allocating participants to either use of the warming mattress or the standard method of warming at Parkland Hospital (heat-retaining caps, warmed intravenous and irrigation fluids, and warmed blankets). The primary outcome of interest was maternal hypothermia. Surgical site infections and neonatal outcomes were also assessed.Results The incidence of maternal hypothermia at the conclusion of the surgery was decreased in the warming mattress group, 67 versus 80% in the standard method group (p = 0.013). There were no significant differences in maternal hypothermia at delivery or on arrival to the postanesthesia care unit. The difference in surgical site infections and neonatal outcomes were nonsignificant.Conclusion Use of a warming mattress reduced the incidence of maternal hypothermia at the conclusion of surgery; however, on admission to the postanesthesia care unit, these effects had dissipated.
Keywords: hypothermia; active warming; cesarean delivery; warming mattress